Transition of Civil-Military Relations for National Development in Nepal - Pant, Sambid Bilas (Unity Journal, 2021)
Before the formation of the professional military and the cavalry, there were citizen militias, an army composed of ordinary citizens in ancient Greece. Numerous scholars in academia have reinforced an ideal relationship between the military and the civilians. Though the traditional roles of the military to protect the national sovereignty and territorial integrity remain crucial, it is important to reassess the roles played by the military in national development in the contemporary liberal democratic societies of the twenty–first century. The objective of the article is to reflect on the changing dynamics of the civil military relationship and discourses in the development of Nepal and to explain why and how the civilian supremacy has been institutionalized over a period of time as enshrined in the Constitution of Nepal. The paper unfolds implications for identifying the means and ways to strengthen the civil-military relationship in the present socio-political context of Nepal. Various information and facts were collected through secondary sources and normative lens was used to analyze the changing dynamics of the civil military relationship and discourses in the development of Nepal. It is revealed that Nepali Army (NA) has been successfully transitioning to a new role by being effectively involved in national development programs through socioeconomic infrastructural development works, by providing humanitarian aid in relief missions and contributing to various national pride projects identified by the government of Nepal and the government must provide resources and mandate NA to carry out various development activities.